FORMATION OF SELF-EDUCATIONAL COMPETENCE OF FUTURE TEACHERS OF PRIMARY GRADES BY MEANS OF INFORMATION AND COMMUNICATION TECHNOLOGIES - N.A. Voropay (Academy of Cognitive and Natural Sciences, 2010)
The article opens the question of the use of informative-communicative technologies in process of formation of the self-educational competence in teachers of primary school.